2022
DOI: 10.3389/fcell.2022.932297
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Diversity of Calretinin Interneurons Generated From Adult Mouse Olfactory Bulb Core Neural Stem Cells

Abstract: Neural stem cells (NSCs) in the olfactory bulb (OB) core can generate mature interneurons in the adult mice brain. The vast majority of these adult generated cells express the calcium-binding protein Calretinin (CalR), and they migrate towards different OB layers. However, these cells have yet to be fully characterized and hence, to achieve this we injected retroviral particles expressing GFP into the OB core of adult animals and found that the CalR+ neurons generated from NSCs mainly migrate to the granule ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…However, it seems unlikely that we labeled less than 0.8 % of the newly generated CR+ neurons that reached the GL by 7 days post-MMZ. Furthermore, OB core neurogenesis generates similar proportions of CR+ PGCs and GCs 36,37 , but GCL CR+ neuron density was not increased at 7 days post-MMZ. Hence, we concluded that enhanced neurogenesis could not account for the rapid increase in CR+ density in the GL and EPL following MMZ treatment.…”
Section: Temporal Pattern Of Changes In Cr+ Neuron Density Following ...mentioning
confidence: 86%
See 2 more Smart Citations
“…However, it seems unlikely that we labeled less than 0.8 % of the newly generated CR+ neurons that reached the GL by 7 days post-MMZ. Furthermore, OB core neurogenesis generates similar proportions of CR+ PGCs and GCs 36,37 , but GCL CR+ neuron density was not increased at 7 days post-MMZ. Hence, we concluded that enhanced neurogenesis could not account for the rapid increase in CR+ density in the GL and EPL following MMZ treatment.…”
Section: Temporal Pattern Of Changes In Cr+ Neuron Density Following ...mentioning
confidence: 86%
“…The first possibility is enhanced integration of CR+ neurons in the GL and EPL. While 7 days is very short for new SVZ-derived neurons to reach the GL, with 90 % of newborn juxtaglomerular neurons retrovirally labeled in the RMS arriving after 7 days post-injection 64 , CR+ neurons are also generated in the OB core 36,37 , enabling them to reach the GL within 7 days. Indeed, we found a 2-fold increase in the density of newborn EdU+CR+ neurons in the GL and EPL at 7 days post-MMZ, suggesting that OB core neurogenesis may be upregulated.…”
Section: Temporal Pattern Of Changes In Cr+ Neuron Density Following ...mentioning
confidence: 99%
See 1 more Smart Citation